High incidence of type 1 diabetes in adolescents and young adults in Eritrea. Issue 7 (6th March 2021) - Mebrahtu, Goitom; Maniam, Jayanthi; James, Steven; Ogle, Graham D.
ABSTRACT: Background: Eritrea has no data on type 1 diabetes incidence in children and youth; therefore, a study was undertaken to determine this in persons aged <25 years. Methods: Data were collected on new type 1 diabetes diagnoses during 2019, from district, provincial and national hospitals. Type 1 diabetes was diagnosed according to standard WHO criteria. No secondary ascertainment source was available. 95% confidence intervals were computed based on approximation to the Poisson distribution, and age and gender effects were analysed with Poisson regression. Results: There were 532 new cases of type 1 diabetes. Mean ± standard deviation (range) age of diagnosis was 16.2 ± 5.7 (1.5–24.9) years, and peak age group was 15–19 years (n = 200, 37.6%), with mode at 18 years. Incidence <15 years was 11.5/100, 000 individuals [9.9–13.2], with the highest incidence in the 10–14 years group (19.0/100, 000 [15.5–23.1]). Incidence then peaked in the 15–19 years age group (50.2/100, 000 [43.5–57.7]) and remained high in the 20–24 years group (46.2/100, 000 [39.0–54.3]). There was a male:female ratio of 1.37 ( p  = 0.001). Two hundred and thirty‐eight (44.7%) presented in diabetic ketoacidosis. Conclusion: Type 1 diabetes incidence in Eritrea is moderate <15 years, and high 15–24 years. The 15–19 and 20–24 years rates appear to be the highest published to date. Given the study was only for one year, further confirmatory prospective information will clarify the situation and document trends. Assessment of the type 1 diabetes phenotypes that are occurring in Eritrea is also indicated.